National Football League Player Market Are Professional Players Still Paid Monopsony Wages? - Miškovský, Karel; Hudík, Marek, 1980-; Koubek, Ivo, 1959-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
The main goal of this thesis is to find out whether National football league players are, even 15 years after the birth of unrestricted free agency, still paid monopsonistic salaries or whether competition among NFL teams eliminated them. After a theoretical discussion, which will help to form expectations about the player market, models in line with the standard theory of labor compensation and with Becker's human capital theory are estimated. The part of the research following the standard theory focuses mainly on estimations of players' marginal revenue product and subsequently on comparison of their wages with their MRP. To do so, OLS regressions, as well as quantile regressions, are run. The part of the research following the human capital theory has a supporting role and is used to further confirm the previous findings. It is represented by OLS player salary estimation. The hypothesis that players under a full control of their teams are still paid salaries below their MRP cannot be rejected, thus confirming a presence of monopsonistic salaries. A significant effect of free agency status on player salaries is also found. Exclusive rights players are paid significantly lower salaries than all free agents, while restricted free agents are paid significantly lower salaries than unrestricted free agents. Superstar players are found to have salaries in excess of their MRP regardless of their free agency status.
Vedoucí práce: Marek Hudík
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses